The effect of using educational motivation methods in the Holy Quran on academic achievement among students of the College of Education (Journal of the College of Basic Education, 2022)
In light of the decline in the level of education in most of the Arab and Islamic countries in general, and our country in particular, to levels that all people of heart and others regret, and in light of the increasing level of frustration among our educated children and in light of their increasing keenness to flex their muscles in confusion and violence and their aversion to school activities. It is more effective to think seriously about methods and alternatives to push them and motivate them to take up their lessons and study programs seriously and enthusiastically. Students in the academic achievement test attributable to the use of